Peran Entrepreneur University dalam Mendongkrak UMKM Kabupaten Magetan melalui Generasi Z - Rohmatiah, Ahadiati; Mutmainah, Mutmainah; Wildaniyati, Arini (Jurnal Samudra Ekonomi dan Bisnis, 2025)
MSMEs need to coexist with higher education institutions in order to face the increasingly fierce competition in the digital-based business landscape. This research aims to understand the role of entrepreneur university in the development of MSMEs in Magetan Regency through Generation Z. The respondents are MSME entrepreneurs. This research uses a qualitative method with descriptive analysis. The research findings indicate the necessity of the role of entrepreneurial universities in the development of MSMEs in Magetan Regency. The role is carried out through students as generation Z. Through their capabilities, MSMEs can grow and more competitive. The capability of this technology involves providing training to MSMEs on how to sell products online, both through social media and e-commerce platforms or marketplaces. There needs to be communication between higher education institutions and MSMEs to be aware of programs related to MSME.